Coconut Shell as a Substitution in Mortar - Theva, Thevaraj; Adi Radhi Fadzilah; Elvin Meringgai Anak Jullin; Nor Farah Atiqah Ahmad (Multidisciplinary Applied Research and Innovation, 2025)
Coconut shell is a waste material with potential uses, particularly as a fine aggregate replacement in mortars. In order to compare the coconut shell mortar alternative with regular mortar, this study has prepared such information. In order to assess the mortar's performance and dependability, five distinct quantities of coconut shell were used to sample the mortars and test them in certain ways. After the mortar's compression and water absorption rate are tested, it is analyzed and contrasted with the control, or more simply put, a regular mortar. The findings indicated that the addition of coconut shell gradually reduced the mortar's performance because the strength of the coconut shell is not as strong as a fine aggregate. It can be conclude that coconut shell can be a substitute for fine aggregate but it is less reliable than what an ordinary mortar can.